Analisis Kesulitan Membaca pada Siswa Kelas Tinggi Sekolah Dasar - Mai Sri Lena; Sahrun Nisa; Latania Yusma Fitas Taftian; Rafina Suciwanisa (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study aims to analyze reading difficulties faced by high school students in elementary school and identify the causal factors. The type of research used is qualitative with descriptive methods. Collecting data using the method of observation, interviews and literature review. The research subject was SDN 14 Kampung Jambak, students of class IV. The results showed that the factors causing students' reading difficulties were 1) not understanding complex words and sentences, 2) lack of understanding of vocabulary, 3) not understanding sentences and text structures, 4) not yet mastering problem-solving skills, especially in reasoning, 5) lack of motivation and interest in reading students, 6) lack of reading practice, and 7) lack of support from the environment. Difficulty reading in high school grades is a complex challenge and requires an appropriate and sustainable approach. Educators, as well as parents, need to work together to identify and provide appropriate support for students who experience reading difficulties. Effective interventions involve approaches that focus on reading strategies and vocabulary mastery. In addition, it is important to create a positive and supportive learning environment, which can increase students' interest and motivation in reading.